A preparation method of Fe-doped In2Se3 two-dimensional material

The chemical vapor phase transfer method incorporates Fe into two-dimensional In2Se3 material, which solves the problem of iron doping difficulties in the prior art, realizes the low-temperature ferromagneticity of In2Se3, and expands its application prospects in magnetic memory devices and other fields.

CN118771314BActive Publication Date: 2025-03-14LANZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410795042.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-03-14
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively incorporate iron into In2Se3 two-dimensional materials, and other impurity elements are easily introduced during doping.

Method used

The Fe powder, In powder and Se powder were mixed with iodine as the transporting agent, and the Fe doped In2Se3 two-dimensional material was prepared by vacuum sealing and chemical gas transport.

Benefits of technology

The successful incorporation of iron elements enables In2Se3 to obtain low-temperature ferromagnetism, providing application prospects for magnetic memory devices, spintronics and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771314B_ABST
    Figure CN118771314B_ABST
Patent Text Reader

Abstract

The present invention provides an Fe-doped In 2 Se 3 A method for preparing a two-dimensional material, the method comprising the following steps: mixing Fe powder, In powder and Se powder, using iodine as a transport agent, and obtaining the material by chemical vapor transport. The present invention provides a method for successfully doping iron into In with a simple preparation process. 2 Se 3 In the method, 2 Se 3 Obtain low-temperature ferromagnetism; it has broad application prospects in magnetic storage devices, spin electronics, magnetic transmission, quantum spin Hall effect and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing Fe-doped In2Se3 two-dimensional material. Background Art

[0002] High-performance memory devices play a key role in the innovation of modern electronics. Faced with the demand for ever-increasing storage capacity, silicon-based technology will soon reach its limits. Two-dimensional materials refer to materials in which electrons can only move freely (planar motion) on a non-nanoscale (1-100nm) in two dimensions. They belong to the category of nanomaterials, including semiconductor materials. Two-dimensional materials are widely used in photodetectors, gas detectors, diodes, transistors, memristors, solar cells, electrocatalysts, photocatalysts and other fields. Two-dimensional materials exhibit unique properties different from ordinary materials, which stems from the quantum confinement effect caused by their ultra-thin thickness. Their ultra-thin characteristics are expected to solve the short channel effect faced by conventional semiconductors, allowing the size of transistors to be further reduced, and have potential application prospects in the field of large-scale integrated circuits.

[0003] In2Se3 is a type of two-dimensional semiconductor material that has received extensive attention and research. It has a large light absorption coefficient and high carrier mobility. The large light absorption coefficient and high carrier mobility have important application value in the fields of optoelectronics and photovoltaics. The large light absorption coefficient can increase the material's ability to absorb light, which is beneficial to the performance improvement of optoelectronic devices, such as photodiodes and photodetectors. High carrier mobility can improve the response speed and efficiency of optoelectronic devices and enhance the performance and stability of the devices. In the photovoltaic field, in solar cells, a large light absorption coefficient can improve the conversion efficiency of light energy and make solar cells use light more fully. High carrier mobility can increase the current output of solar cells and increase the power output of the battery. In the field of optical communications, a large light absorption coefficient can enhance the transmission and detection of optical signals, and a high carrier mobility can improve the response speed and transmission efficiency of optical communication devices. A large light absorption coefficient and high carrier mobility can also be applied to the field of optical sensors to improve the sensor's ability to detect and respond to optical signals and improve the sensitivity and stability of the sensor. Large light absorption coefficient and high carrier mobility have important application prospects in optoelectronics, photovoltaics, optical communications, optical sensors and other fields, which can bring more efficient and stable optoelectronic devices and systems. Due to the piezoresistive effect, it can also be used in strain sensors and other fields.

[0004] Multiferroic materials show the orderly coexistence of two or more ferroelectric properties such as ferroelectricity, ferromagnetism, and ferroelasticity. The mutual coupling between multiple order parameters will produce new effects. For example, ferroelectricity and magnetism are coupled to produce magnetoelectric effect, that is, the material produces electric polarization under the action of an external magnetic field, or the external electric field regulates the magnetic properties. Magnetoelectric materials are a new type of multifunctional material. They can not only be used in the application field of single ferroic materials, but also show great application prospects in the fields of new magneto-electric sensor devices, spintronic devices, and new information storage devices. In2Se3 itself is a diamagnetic material, so it can be made ferromagnetic by doping with iron, and magnetoelectric coupling can be achieved to develop smaller, faster, and more efficient data storage devices.

[0005] The traditional preparation method for two-dimensional materials is chemical vapor deposition, which has the main problems of being difficult to dope iron into indium triselenide and the possibility of other impurity elements being doped during the doping process. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing Fe-doped In2Se3 two-dimensional material.

[0007] A method for preparing Fe-doped In2Se3 two-dimensional material comprises the following steps: mixing Fe powder, In powder and Se powder, using iodine as a transport agent, and obtaining the material by chemical vapor transport.

[0008] According to some embodiments of the preparation method of the present invention, the purity of the iron (Fe) powder is ≥99.95wt%.

[0009] According to some embodiments of the preparation method of the present invention, the purity of the indium (In) powder is ≥99.99wt%.

[0010] According to some embodiments of the preparation method of the present invention, the purity of the selenium (Se) powder is ≥99.999wt%.

[0011] According to some embodiments of the preparation method of the present invention, the steps include: mixing Fe powder, In powder, Se powder and iodine and adding them into a quartz ampoule, vacuum sealing the quartz ampoule, and placing the vacuum sealed quartz ampoule into a vacuum tube furnace for chemical vapor transport treatment.

[0012] According to some embodiments of the preparation method of the present invention, the temperature of the chemical vapor transport is 850-950°C; for example, 850°C, 900°C, 950°C.

[0013] According to some embodiments of the preparation method of the present invention, the temperature of the chemical vapor transport is 920-950°C; for example, 920°C, 930°C, 940°C, 950°C.

[0014] According to some embodiments of the preparation method of the present invention, the operation of the chemical vapor transport is: heating to 850-950°C at a heating rate of 1-3°C / min, keeping at this temperature for 6-8 days, and then cooling.

[0015] According to some embodiments of the preparation method of the present invention, the molar ratio of the Fe powder, the In powder and the Se powder is 1:(12-16):(18-25); for example, 1:12:18, 1:13:19, 1:13:20, 1:14:22, 1:15:23, 1:18:25.

[0016] According to some embodiments of the preparation method of the present invention, the molar ratio of the Fe powder, the In powder and the Se powder is 1:14.25:21.38.

[0017] According to some embodiments of the preparation method of the present invention, the molar ratio of the Fe powder to the In powder is 1:(13-15); for example, 1:13, 1:14, 1:14.25, 1:15.

[0018] According to some embodiments of the preparation method of the present invention, the molar ratio of the iodine to the Fe powder is (0.1-0.3):1; for example, 0.1:1, 0.2:1, 0.23:1, 0.24:1, 0.28:1, 0.3:1.

[0019] According to some embodiments of the preparation method of the present invention, the molar ratio of the iodine to the Fe powder is 0.26:1.

[0020] According to some embodiments of the preparation method of the present invention, the cooling treatment is natural cooling to 20-25° C. in a furnace.

[0021] The beneficial effects of the present invention include:

[0022] (1) The present invention provides a method for successfully doping iron into In2Se3 with a simple preparation process, so that In2Se3 can obtain low-temperature ferromagnetism.

[0023] (2) The two-dimensional material prepared by the preparation method of the present invention has broad application prospects in the fields of magnetic storage devices, spin electronics, magnetic transmission, quantum spin Hall effect, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the Fe-doped In2Se3 two-dimensional material prepared in Example 1 of the present invention;

[0025] Figure 2 This is an ultrastructure diagram of the Fe-doped In2Se3 two-dimensional material sample prepared in Example 1 of the present invention; Figure 2 a is a high-angle annular dark field image, Figure 2 b is the corresponding distribution diagram of Fe element, Figure 2 c is the distribution diagram of In element, Figure 2 d is the distribution diagram of Se element;

[0026] Figure 3 for Figure 2 Energy dispersive X-ray spectroscopy (EDS) spectra of the selected area in a;

[0027] Figure 4 for Figure 2 Electron energy loss spectroscopy (EELS) spectrum of Fe element in the selected area in a;

[0028] Figure 5 A high-angle annular dark field scanning transmission electron microscopy image (HAADF-STEM) of the Fe-doped In2Se3 two-dimensional material prepared in Example 1 of the present invention;

[0029] Figure 6 The EDS mapping test results of the Fe-doped In2Se3 two-dimensional material prepared in Example 1 of the present invention;

[0030] Figure 7 The superconducting quantum interference device (SQUID) test results of the Fe-doped In2Se3 two-dimensional material prepared in Example 1 of the present invention;

[0031] Figure 8 This is the EDS mapping test result of the two-dimensional material prepared in Comparative Example 1 of the present invention;

[0032] Fig. 9 This is the EDS mapping test result of the two-dimensional material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0034] Example 1

[0035] Step 1, add 0.4922g of In powder (purity ≥99.99wt%), 0.5079g of Se powder (purity ≥99.999wt%), 0.0168g of Fe powder (purity ≥99.95wt%) and 0.02g of iodine ball into a quartz ampoule;

[0036] Step 2, vacuum sealing the quartz ampoule in step 1 using a vacuum sealing device;

[0037] Step three, place the quartz ampoule containing the raw materials after vacuum sealing in step two into a vacuum tube furnace, heat it from room temperature to 950°C at a heating rate of 2°C / min, keep it at this temperature for 7 days, and then cool it to room temperature (20-25°C) in the furnace to obtain In2Se3 two-dimensional material with an Fe doping mass percentage concentration of 7%.

[0038] 1. Physical characterization of the Fe-doped In2Se3 two-dimensional material described in Example 1

[0039] The Fe-doped In2Se3 two-dimensional material prepared in Example 1 was taken out from the quartz ampoule tube, washed with anhydrous ethanol for several times, the washed sample was placed in a beaker, dried in an oven at 50°C and sealed for the next step of testing and characterization.

[0040] 1.1 SEM image of Fe-doped In2Se3 two-dimensional material prepared in Example 1, as shown in Figure 1 As shown:

[0041] from Figure 1 It can be seen that the material prepared in Example 1 of the present invention is in a flaky form as a whole.

[0042] 1.2 The Fe-doped In2Se3 two-dimensional material prepared in Example 1 was exfoliated by a mechanical exfoliation method commonly used for two-dimensional materials to obtain a nanosheet sample. The transmission electron micrograph of the obtained nanosheet sample and the corresponding distribution diagram of Fe, In and Se elements are as follows: Figure 2 As shown, Figure 2 The energy dispersive X-ray spectroscopy (EDS) spectrum and the electron energy loss spectroscopy (EELS) spectrum of the Fe element in the selected area in a are shown in Figure 2. Figure 3 and Figure 4 As shown:

[0043] from Figure 2 , Figure 3 and Figure 4It can be seen that the elemental analysis of the prepared nanosheets by energy dispersive X-ray spectroscopy (EDS) shows that the nanosheet samples are composed of In, Se, and Fe elements; the electron energy loss spectrum (EELS) test results show that the sample contains Fe elements. The EDS and EELS test results show that the Fe element is successfully doped. The corresponding EDS element mapping image Figure 2 b- Figure 2 d clearly shows the distribution of element Fe, element In, and element Se.

[0044] 1.3 High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of the Fe-doped In2Se3 two-dimensional material prepared in Example 1, as shown Figure 5 As shown; the EDS mapping test results of the material are as follows Figure 6 b- Figure 6 d; the EDS mapping overlap images of the In element and the Fe element, as shown in Figure 6 As shown in e:

[0045] from Figure 5 and Figure 6 It can be seen from the figure that the HAADF-STEM of the material shows a 5-layer structure, which is consistent with the five-layer structure of Se-In-Se-In-Se of In2Se3; from the EDS mapping test results, it can be seen that the position of the Fe atoms coincides with the In atoms, indicating that the Fe atoms are doped at the position of the In atoms.

[0046] 1.4 Using a superconducting quantum interference device (SQUID), the Fe-doped In2Se3 two-dimensional material prepared in Example 1 was subjected to OOP (out-of-plane) and IP (in-plane) MH tests at a temperature of 50K. The test results are shown in Figure 7 As shown:

[0047] from Figure 7 It can be seen that the change trend of the hysteresis loop is consistent with that of ferromagnetic materials, indicating that the material has magnetism through doping. At the same time, it can be seen that IP is in the easy magnetization direction relative to OPP. The appearance of this in-plane and out-of-plane difficult and easy axis originates from the asymmetry of the hexagonal crystal structure. This asymmetry makes the magnetocrystalline anisotropy in various directions have great differences.

[0048] Example 2

[0049] Step 1: Add 1.4766 g of In powder (purity ≥ 99.9 wt%), 1.5231 g of Se powder (purity ≥ 99.9 wt%), 0.3 g of Fe powder (purity ≥ 99.9 wt%) and 0.02 g of iodine ball into a quartz ampoule;

[0050] Step 2, vacuum sealing the quartz ampoule in step 1 using a vacuum sealing device;

[0051] Step three, place the vacuum-sealed quartz ampoule containing the raw materials in step two into a vacuum tube furnace, heat it from room temperature to 950°C at a heating rate of 2°C / min, keep it at this temperature for 7 days, and then cool it to room temperature (20-25°C) in the furnace to obtain Fe-doped In2Se3 two-dimensional material.

[0052] Example 3

[0053] Step 1, add 0.4922g of In powder (purity ≥ 99.9wt%), 0.5079g of Se powder (purity ≥ 99.9wt%), 0.0168g of Fe powder (purity ≥ 99.9wt%) and 0.02g of iodine ball into a quartz ampoule;

[0054] Step 2, vacuum sealing the quartz ampoule in step 1 using a vacuum sealing device;

[0055] Step three, placing the vacuum-sealed quartz ampoule containing the raw materials in step two into a vacuum tube furnace, heating it from room temperature to 850°C at a heating rate of 2°C / min, keeping it at this temperature for 7 days, and then cooling it to room temperature (20-25°C) in the furnace. It was found that no reaction occurred and no target product was obtained.

[0056] Comparative Example 1

[0057] The difference between the method described in comparative example 1 and the method described in example 1 of the present application is that ferric chloride is used instead of iron powder;

[0058] Specifically:

[0059] Step 1: Add 0.4922 g of In powder (purity ≥ 99.99 wt%), 0.5079 g of Se powder (purity ≥ 99.999 wt%), 0.04866 g of FeCl3 and 0.02 g of iodine ball into a quartz ampoule.

[0060] Step 2: vacuum seal the quartz ampoule prepared in step 1 using a vacuum sealing device.

[0061] Step three, place the vacuum-sealed quartz ampoule containing the raw materials in step two into a vacuum tube furnace, heat it from room temperature to 950°C at a heating rate of 2°C / min, keep it at this temperature for 7 days, and then cool it to room temperature (20-25°C) in the furnace to obtain a two-dimensional material with an Fe-doped mass percentage concentration of 1.38%.

[0062] The element content of the two-dimensional material in Comparative Example 1 was analyzed using an EDS spectrometer. The analysis results are shown in Table 1:

[0063] Table 1

[0064] Z element X-ray line families Atomic fraction Atomic Error Quality score Quality Error Fitting error 17 Cl K 26.25% 1.76% 10.66% 0.92% 0.45% 26 Fe K 2.16% 0.32% 1.38% 0.22% 2.22% 34 Se K 15.12% 1.92% 13.68% 1.9% 0.66% 49 In L 56.47% 2.97% 74.28% 2.51% 0.75%

[0065] The EDS mapping test results of the two-dimensional material described in Comparative Example 1 are as follows: Figure 8 As shown:

[0066] From Table 1 and Figure 8 It can be seen that the two-dimensional material prepared in Comparative Example 1 contains a small amount of Fe and Cl, and the content of Cl is relatively high, with an Fe doping concentration of 1.38%. This indicates that it is difficult to obtain Fe-doped In2Se3 two-dimensional materials using ferric chloride, and the presence of Cl in the product makes the product impure. In addition, anhydrous ferric chloride is very easy to absorb water. A small amount of it will absorb water and become small droplets when exposed to the air for a short time, which is not conducive to experimental operation.

[0067] Comparative Example 2

[0068] The only difference between Comparative Example 2 and the method described in Example 1 of the present application is that a horizontal double-zone tube furnace is used instead of a vacuum tube furnace.

[0069] Specifically:

[0070] 0.05 g of Se powder was put into a quartz boat, 0.4 g of In powder and 0.02 g of Fe powder were weighed and ground and mixed evenly in a mortar, and then 0.022 g of the mixed powder was weighed and put into a quartz boat, and the material was grown on the fluorophlogopite sheet using the CVD method.

[0071] During the reaction, Se powder was placed in the low temperature zone and the mixed powder was placed in the high temperature zone. The reaction temperature was heated from room temperature to 120 degrees Celsius in 15 minutes in the low temperature zone, then raised to 300 degrees Celsius in five minutes, kept warm for 20 minutes, and then cooled down. The high temperature zone was heated from room temperature to 710 degrees Celsius in 20 minutes, kept warm for 20 minutes, and then cooled down.

[0072] During the reaction, the gas flow was controlled by purging with nitrogen for two minutes before heating began. The nitrogen flow was then set to 120 sccm. After nitrogen flow for 40 minutes, the nitrogen flow was then 120 sccm until the temperature dropped to room temperature.

[0073] The element content of the two-dimensional material in Comparative Example 2 was analyzed using an EDS spectrometer. The analysis results are shown in Table 2:

[0074] Table 2

[0075] Z element X-ray line families Atomic fraction Atomic Error Quality score Quality Error Fitting error 26 Fe K 83.67% 1.51% 73.77% 2.16% 0.64% 34 Se K 5.96% 0.9% 7.44% 1.09% 7.36% 49 In L 10.37% 1.19% 18.79% 1.95% 2.24%

[0076] The EDS mapping test results of the two-dimensional material described in Comparative Example 2 are as follows: Fig. 9 As shown:

[0077] From Table 2 and Fig. 9 It can be seen that more than 80% of the product obtained in Comparative Example 2 is iron, that is, iron-doped In2Se3 cannot be obtained by the method described in Comparative Example 2.

[0078] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing Fe-doped In2Se3 two-dimensional material, comprising the following steps: Fe powder, In powder, Se powder and iodine are mixed and added into a quartz ampoule, the quartz ampoule is vacuum-sealed, and the vacuum-sealed quartz ampoule is placed into a vacuum tube furnace for chemical vapor transport treatment; The molar ratio of the Fe powder, the In powder and the Se powder is 1:(12-16):(18-25).

2. The preparation method according to claim 1, characterized in that: The temperature of the chemical vapor transport is 850-950°C.

3. The preparation method according to claim 1, characterized in that: The temperature of the chemical vapor transport is 920-950°C.

4. The preparation method according to claim 2, characterized in that: The operation of the chemical vapor transport is: heating to 850-950° C. at a heating rate of 1-3° C. / min, keeping at this temperature for 6-8 days, and then cooling.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of the Fe powder to the In powder is 1:(13-15).

6. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of the Fe powder to the In powder is 1:14.

25.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of the iodine to the Fe powder is (0.1-0.3):

1.

8. The preparation method according to claim 7, characterized in that: The molar ratio of the iodine to the Fe powder is 0.26:

1.

9. The preparation method according to claim 4, characterized in that: The cooling treatment is natural cooling to 20-25° C. in the furnace.

Citation Information

Patent Citations

  • Growth method of two-dimensional ferromagnetic material Fe3GeTe2 and Co-doped Fe3-xCoxGeTe2 single crystal

    CN111593402A